2017
DOI: 10.1007/jhep04(2017)125
|View full text |Cite
|
Sign up to set email alerts
|

Groomed jets in heavy-ion collisions: sensitivity to medium-induced bremsstrahlung

Abstract: We argue that contemporary jet substructure techniques might facilitate a more direct measurement of hard medium-induced gluon bremsstrahlung in heavy-ion collisions, and focus specifically on the "soft drop declustering" procedure that singles out the two leading jet substructures. Assuming coherent jet energy loss, we find an enhancement of the distribution of the energy fractions shared by the two substructures at small subjet energy caused by hard medium-induced gluon radiation. Departures from this approx… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 96 publications
2
66
0
Order By: Relevance
“…When studying the consequences of the incoherent energy loss on the z g distribution, Refs. [10,11] obtained results which are qualitatively similar to the curve denoted as "energy loss only" in our Fig. 15, right, i.e.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…When studying the consequences of the incoherent energy loss on the z g distribution, Refs. [10,11] obtained results which are qualitatively similar to the curve denoted as "energy loss only" in our Fig. 15, right, i.e.…”
Section: Discussionsupporting
confidence: 84%
“…(2.16)). 10 The factorᾱ in the I0 is associated to the further fragmentation of the gluons emitted from the main parton and therefore remains αsCA/π independently of the leading parton. 11 We have used the same hard-scattering spectrum for both the pp baseline and the PbPb sample.…”
Section: The Nuclear Modification Factor R Aamentioning
confidence: 99%
“…The more important contribution, however, comes from adding the recoiling partons. 6 In Jewel+Pythia we see no sign of medium induced bremsstrahlung contributing to the effect, as advertised in [52].…”
Section: Groomed Shared Momentum Fraction Z Gmentioning
confidence: 68%
“…In p+p collisions, this method has been studied in some detail [49,51], but in heavy ion collisions the exact meaning of the grooming procedure is not obvious, due to the presence of the fluctuating underlying heavy ion event and the increased soft sector, that the procedure tries to remove. Recent analytical studies [52] have shown that grooming increases the sensitivity to medium induced gluon bremsstrahlung thus experimentally opening up different avenues to directly probe the effect of the medium on a jet by jet basis. In Jewel, however, a different story unfolds.…”
Section: Groomed Shared Momentum Fraction Z Gmentioning
confidence: 99%
“…Both on the experimental [5][6][7][8] and the theoretical side [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], significant progress has been made recently in improving our understanding of soft drop groomed jet observables. In the heavy-ion community, soft drop groomed jet substructure observables have also received increasing attention from both experiment [25][26][27][28] and theory [29][30][31][32][33][34][35][36][37][38][39]. Jet grooming techniques can be used to isolate different aspects of jet quenching and may help to discriminate between different model assumptions [40].…”
Section: Introductionmentioning
confidence: 99%